Efficient Low-pH Iron Removal by a Microbial Iron Oxide Mound Ecosystem at Scalp Level Run - Grettenberger, Christen L. (Appl Environ Microbiol, 2017)
Acid mine drainage (AMD) is a major environmental problem affecting tens of thousands of kilometers of waterways worldwide. Passive bioremediation of AMD relies on microbial communities to oxidize and remove iron from the system; however, iron oxidation rates in AMD environments are highly variable among sites. At Scalp Level Run (Cambria County, PA), first-order iron oxidation rates are 10 times greater than at other coal-associated iron mounds in the Appalachians. We examined the bacterial community at Scalp Level Run to determine whether a unique community is responsible for the rapid iron oxidation rate. Despite strong geochemical gradients, including a >10-fold change in the concentration of ferrous iron from 57.3 mg/liter at the emergence to 2.5 mg/liter at the base of the coal tailings pile, the bacterial community composition was nearly constant with distance from the spring outflow. Scalp Level Run contains many of the same taxa present in other AMD sites, but the community is dominated by two strains of Ferrovum myxofaciens, a species that is associated with high rates of Fe(II) oxidation in laboratory studies. IMPORTANCE Acid mine drainage pollutes more than 19,300 km of rivers and streams and 72,000 ha of lakes worldwide. Remediation is frequently ineffective and costly, upwards of $100 billion globally and nearly $5 billion in Pennsylvania alone. Microbial Fe(II) oxidation is more efficient than abiotic Fe(II) oxidation at low pH (P. C. Singer and W. Stumm, Science 167:1121–1123, 1970, https://doi.org/10.1126/science.167.3921.1121). Therefore, AMD bioremediation could harness microbial Fe(II) oxidation to fuel more-cost-effective treatments. Advances will require a deeper understanding of the ecology of Fe(II)-oxidizing microbial communities and the factors that control their distribution and rates of Fe(II) oxidation. We investigated bacterial communities that inhabit an AMD site with rapid Fe(II) oxidation and found that they were dominated by two operational taxonomic units (OTUs) of Ferrovum myxofaciens, a taxon associated with high laboratory rates of iron oxidation. This research represents a step forward in identifying taxa that can be used to enhance cost-effective AMD bioremediation.